A Snapshot of Poverty Among Québec’s English-speaking Communities - Provincial Employment Roundtable (PERT) (2023)
Québec is home to more than 1.2 million English speakers, representing 14.9% of the province’s population. Data from the 2021 Census of Canada indicates that English-speaking Quebecers occupy a more precarious economic position than their French-speaking counterparts, experiencing higher rates of poverty and unemployment and earning lower median incomes. Research conducted by PERT has highlighted some of the specific barriers and challenges English speakers face regarding labour market integration and retention in Québec, including lack of French-language training for the workforce, lack of English-language employability services, lack of English-language vocational training, and lack of wrap-around support services. These employment challenges impact English speakers' labour market outcomes and are associated with higher rates of poverty. Furthermore, many of these challenges, especially lack of wrap-around supports (e.g. housing or food security), can directly contribute to – and result from – poverty.

Un aperçu de la pauvreté dans les communautés d'expression anglaise du Québec - Provincial Employment Roundtable (PERT) (2023)
Le Québec compte plus de 1,2 million de Québécois d’expression anglaise, soit 14,9 % de la population de la province. Les données du recensement du Canada de 2021 indiquent que les Québécois d’expression anglaise occupent une position économique plus précaire que leurs homologues francophones, qu'ils connaissent des taux de pauvreté et de chômage plus élevés et qu'ils gagnent des revenus médians plus faibles. Les recherches menées par PERT ont mis en évidence certains des obstacles et défis spécifiques auxquels sont confrontés les Québécois d’expression anglaise en matière d'intégration et de rétention sur le marché du travail au Québec, notamment le manque de formation en français pour the marché du travail, le manque de services d'employabilité en anglais, le manque de formation professionnelle en anglais et le manque mesures de soutien globales. Ces difficultés d'emploi ont un impact sur les résultats des Québécois d’expression anglaise sur le marché du travail et ont été associées à des taux de pauvreté plus élevés. En outre, nombre de ces difficultés, en particulier l'absence de services d'accompagnement (par exemple, le logement ou la sécurité alimentaire), peuvent directement contribuer à la pauvreté et en résulter.

Cartographie des aides à l'emploi pour les communautés racialisées et immigrantes d'expression anglaise du Québec - Provincial Employment Roundtable (PERT) (2023)
L'emploi est de plus en plus devenu une question prioritaire pour les communautés d’expression anglaise du Québec, qui continuent d'être confrontées à des taux de chômage plus élevés et à des revenus plus faibles que la majorité francophone. Les données sur la population active concernant les immigrants d'expression anglaise et les personnes racialisées indiquent que ces groupes ont tendance à éprouver des difficultés encore plus grandes sur le marché du travail. Étant à la fois minorités linguistiques et immigrants et/ou personnes racialisées, elles naviguent sur un marché du travail francophone tout en faisant face à des défis tels que la discrimination et le manque de ressources. Dans ce contexte, les aides à l'emploi, telles que les ateliers d'employabilité, l'aide à la recherche d'emploi et l'accompagnement professionnel, jouent un rôle important dans la lutte contre les obstacles au marché du travail. Pour les immigrants d’expression anglaise et les personnes racialisées, les aides à l'emploi qui reconnaissent leurs expériences uniques et leur position sur le marché du travail peuvent avoir un impact positif sur leurs résultats sur le marché du travail. Cette recherche vise à mieux comprendre la situation des immigrants et des Québécois d’expression anglaise racialisés sur le marché du travail au Québec et à évaluer les mesures de soutien à l'emploi disponible pour ces communautés.

Les immigrants et le français au Québec : un portrait statistique complexe et nuancé qui s’impose - Corbeil, Jean-Pierre; Houle, René (90 e Congrès de l’ Acfas, 2023)

Resolution 2023-08 : Accomodate Immigrant and Refugee Children - Quebec Federation of Home and School Associations (QFHSA) (2023)

Résolution 2022–06 : Enfants ukrainiens immigrants - Quebec Federation of Home and School Associations (QFHSA) (2022)

New Residents Package - Regional Association of West Quebecers (RAWQ) (2021)

2020-2021 Annual Report - The English Speaking Catholic Council (ESCC) (2021)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

Report on the 2019 NDG Community Health Forum - NDG Community Council (NDGCC) (2019)
On October 20th 2019, the NDG Senior Citizens’ Council sponsored a community health forum organized in collaboration with the NDG Working Group on Health and the NDG Community Council. The African-Canadian Development and Prevention Network (ACDPN), Hear Entendre Quebec and Prevention NDG were also engaged regularly throughout the process in order to address issues of access and cultural sensitivity in the discussions. The goal of the forum was to inform the residents of NDG and surrounding areas about the resources that exist through institutions supported by the Centre Intégré Universitaire de Santé et de Services Sociaux for the Center-West of Montreal (Hereafter CIUSSS-CODIM), as well as many of the local community organizations, in particular as they relate to health and health access. Further, the event aimed to create a discourse between the health and social service providers, encouraging participants to open a dialogue regarding the gaps in services experienced by residents so that the Working Group on Health could be better informed for future action.

Social Initiatives for Vulnerable English-speaking Youth Seniors Newcomers / Initiatives sociales pour jeunes aînés nouveaux arrivants - Quebec Community Groups Network (QCGN) (2019)
The Community Innovation Fund (CIF) has helped Quebec’s English-speaking communities transform social innovation into action through the development of skills. The Fund financed 10 innovative projects that targeted particular needs and priorities of vulnerable English-speaking youth, seniors and newcomers. Each project, in its own way, served to improve job skills or help maintain basic socio-economic security of English-speaking Quebecers. In the following pages, you will learn more about these projects – what they set out to do, what they’ve accomplished and how they served to enhance the vitality of English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

Network News - Quebec Community Groups Network (QCGN) (2018)

Québec Health 101 Guide - Jeffery Hale Community Services; Community Wellness Centre; Voice of English-speaking Quebec (VEQ) (2018)
This guide and the accompanying presentation were developed with the intention of helping newcomers navigate the medical system here in Québec City with a little more ease and efficiency. This project was a joint effort between Jeffery Hale Community Services, the Community Wellness Centre and the Voice of English-speaking Québec. This document was inspired by the Valcartier Family Centre Health Guide.

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

Presentation by Youth Employment Services (YES) to the Standing Senate Committee on Official Languages and the English-speaking Community in Quebec - Youth Employment Services (YES) (2017)
YES (Youth Employment Services) is a non-for-profit charity whose mission is to enrich the community by providing English-language services to help people find jobs and start small and medium size businesses.
Keywords: Official Language Minority Community (OLMC)

Annex - List of Funded Projects - Quebec Community Groups Network (QCGN) (2017)

Social Initiatives to Address Needs of Vulnerable English-speaking Youth, Seniors and Newcomers - Quebec Community Groups Network (QCGN) (2017)

Opportunities & Obstacles Facing English-Speaking Newcomers Launching Small to Medium Enterprises (SMEs) in Quebec - Association for Canadian Studies (2017)
The objective of this research study is to identify the key barriers and opportunities that English-speaking newcomers face when launching or planning to launch small to medium enterprises (SMEs) in Quebec. We intend to use the information gathered by this study to assist policy makers and entrepreneurship service providers in supporting newcomers (recent immigrants who arrived in the past five years) in the creation and growth of SMEs, leading to a stronger entrepreneurial society and economy in Quebec.

QCGN to Host Conference on Community Engagement and the Integration of Newcomers - Quebec Community Groups Network (QCGN) (2017)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

Community Innovation Fund Seeking Proposals to Better Serve Vulnerable Youth, Seniors/Caregivers or Newcomers in Quebec's English-language Communities - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Quebec's English-speaking Communities Need Support to Integrate Newcomers - Quebec Community Groups Network (QCGN) (2015)
Keywords: Official Language Minority Community (OLMC)

Newly Arrived in NDG : Resource Guide - NDG Community Council (NDGCC) (2014)

Nouvellement arrivé à NDG : Guide des ressources - NDG Community Council (NDGCC) (2014)

Building Youth Resiliency and Community Vitality Within Montreal’s English Language Population : The YES Experience with Youth Seeking to Improve their Work Situation - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2013)
In response to an increase in the number of clients’ experiencing mental health challenges in the course of their job search YES (through CHSSN) has commissioned this report to establish an evidence-based profile of the youth that they serve. At the present time, YES uses limited resources to offer additional support through a focus group that is designed for clients who are experiencing symptoms such as decreased motivation, anxiety, social isolation and diminished confidence in dealing with the transition process.
Keywords: Official Language Minority Community (OLMC)

Brief Regarding the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Voice of English-speaking Quebec (VEQ) (2013)
The purpose of this brief is to highlight the potential impacts that the proposed Bill 14 could have on the minority English-speaking community of the Greater Quebec City region. As the preeminent interest group representing English-speakers in the Quebec City region, VEQ has carefully analyzed all the modifications included in the proposed Bill 14 and has consulted its membership, community and many of its key partners in order to present this comprehensive evaluation of the impacts that Bill 14 could have on our community. It is our opinion that Bill 14, if adopted in its present form, will have several negative consequences on the vitality of our community and on the capacity of English speakers to continue to be contributing citizens of our region. In addition, we sincerely believe that Bill 14 will also have a real negative impact on the capacity of our entire region to attract and retain English-speaking immigrants and migrants which will directly affect the economic prosperity of the Quebec City region.
Keywords: Official Language Minority Community (OLMC)

A Community Dialogue About Retention and Integration of Newcomers to the English-speaking Communities of Quebec - Quebec Community Groups Network (QCGN) (2011)

Presentation to the Standing Committee on Official Languages on Immigration as a Development Tool in Official Language Minority Communities - Donnelly, Robert; Dupuis, Michelle (Quebec Community Groups Network (QCGN), 2010)

Canada's New Official Languages Plan : Will it Help Quebec? - Alliance Quebec (AQ) (2003)

Avonelle Titus : A Victory for the English-speaking Community - Alliance Quebec (AQ) (1999)

Alliance Quebec Fund for Avonelle Titus - Alliance Quebec (AQ) (1999)

Alliance Quebec Denounces an Alarmist La Presse Story - Alliance Quebec (AQ) (1999)

Brief on the Green Paper of Immigration to the Special Joint Committee on Immigration Policy by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1975)
Any new Immigration Act ought to satisfy criteria which will make its spirit easily grasped by all people interested in the subject: it ought to be concise; it ought to spell out clearly a set of positive and basic principles governing regulations which will be issued from time to time to implement the Act - it being recognized that while the regulations themselves must be revised from time to time to make the Act applicable to changing circumstances, yet these must at all time represent in practice the spirit of the Act. Thus we agree with what the Green Paper indicated (Highlights Vol. 1 p. 18).